Mekanisme Safeguard World Trade Organization dalam Kaitannya dengan Kedaulatan Pangan di Indonesia - Nur Gemilang Mahardhika (Fakultas Hukum Universitas Islam Indonesia, 2025)
Indonesia faces serious food security issues, especially related to rice imports. Although Indonesia has great agricultural potential, domestic food production is not sufficient for domestic needs. This paper aims to analyze how the safeguard mechanism in the World Trade Organization (WTO) Agreement can be used to protect the interests of farmers and the domestic food industry. This study will discuss two core issues, namely how the safeguard mechanism is regulated in the WTO agreement and how the WTO safeguard mechanism can be applied to food import policies in Indonesia as a developing country. The results of this study are expected to contribute to national food policies and improve Indonesia's food sovereignty.Keywords: Food Sovereignty, Safeguard, World Trade Organization.